Two promising approaches in the treatment of myocardial infarction: stem cells and gene therapy - Gao, Shan; Li, Dan; Wang, Bingkai; Zhang, Hao; Chen, Lu (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular diseases (CVDs), characterized by a high incidence rate and high mortality, have become the leading cause of death globally. CVDs include coronary heart disease, stroke, hypertension, and peripheral vascular diseases. In China, the death rate of CVDs ranks the first in all major diseases. At present, the main methods to treat ischemic heart disease are drug therapy, intervention and operation. These methods only alleviate symptoms of heart failure and myocardial ischemia and improve patients' quality of life by partially restoring myocardial reperfusion. Due to the extensive irreversible necrosis of myocardial cells caused by ischemia and hypoxia, these methods cannot reverse the damage, resulting in suboptimal long-term outcomes. Although mature cardiomyocytes have been proved not to be terminally differentiated cells, they have very limited ability of regeneration and proliferation, so they can not completely replace the damaged myocardium and restore the contractile function. Although heart transplantation can replace the damaged heart, its clinical application and promotion are limited by the source of donor, expensive cost, immune rejection, and ethical problems. It has become an urgent task for clinical medicine to seek new and better treatment. The main content of this paper is to explore the application of stem cells and gene technology in the treatment of myocardial infarction (MI).